Development mechanism of internal local corrosion of X80 pipeline steel. (15th July 2020) - Tan, Zhuowei; Yang, Liuyang; Zhang, Dalei; Wang, Zhenbo; Cheng, Frank; Zhang, Mingyang; Jin, Youhai
Graphical abstract: Highlights: The influence of surface morphology on local flow field after local corrosion is simulated. High shear stress induced by local defects is not sufficient to destroy dense corrosion scales. Evaluate the mechanical strength of loose corrosion scales consisting of Fe3 C and FeCO3 is between 137.2 Pa and 148.3 Pa. Cavitation caused by release of CO2 in solution under flow is the reason to destruction of dense corrosion scale. Abstract: The occurrence and development mechanism of internal local corrosion has always been a controversial topic, and especially under flow conditions. In this paper, an improved high shear force loop was experimentally used, and local flow field is induced by simulating corrosion defects on the surface of X80 pipeline steel specimens. The characteristics of corrosion products deposited on the surface of specimens in CO2 -saturated NACE solution were investigated by means of electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy dispersive spectrometry (EDS). The 3D micromorphology of the corrosion test surface after remove the corrosion scale used to measure the size of localized corrosion pit. Under the influence of local defects, the wall shear stress (WSS) and turbulent kinetic energy of local flow fields enhanced significantly, and pressure fluctuations in local flow field were induced. The results showed that the characteristics of surface corrosion products varied with flow velocity. The corrosion scales formed in various regions of specimens with defects exhibited different surface micro-morphologies and chemical compositions. Overall, these data offer new perspectives for better understanding the mechanisms behind local corrosion.